Bioinformatics analysis across pan-cancer and experimental validation in hepatocellular carcinoma revealed the oncogenic role of SF3B6 - Tu, Linshuang; Luo, Jiefu; Yin, Ya; Yu, Huihong (Frontiers in Pharmacology, 2025)
BackgroundSplicing factor 3b subunit 6(SF3B6), a subunit of the SF3B complex, regulates the process of RNA splicing by recognizing the branch point adenosine in pre-mRNA and facilitating the interaction between U2 snRNA and the branch point sequence. Currently, there is no systematic multi-omics study exploring the diagnostic, prognostic, and immunotherapy predictive value of SF3B6 in pan-cancer, nor is its role in hepatocellular carcinoma (HCC) clear.MethodsWe utilized various databases to systematically examine the expression and genetic variation of SF3B6 across multiple cancer types, assessing its relationship with diagnosis, prognosis, immune infiltration, immunotherapy response, and associated signaling pathways. Additionally, we investigated the correlation between SF3B6 and prognosis, clinicopathological features, and treatment responses in HCC, as well as the roles of its related alternative splicing isoforms. Finally, we conducted in vitro experiments to validate the effects of SF3B6 on the proliferation, migration, invasion, apoptosis, and cell cycle progression of liver cancer cells.ResultsResults indicate that SF3B6 was highly expressed in various cancers and regulated by copy number variations and DNA methylation. The elevated expression of SF3B6 demonstrated predictive value for cancer diagnosis, prognosis, and responses to immunotherapy. Functional enrichment analysis suggests that SF3B6 was closely associated with pathways related to tumor immunity, tumor metabolism, and cell cycle. Additionally, high SF3B6 expression was an independent risk factor for overall survival and correlated with poor alpha-fetoprotein levels, pathological grading, clinical staging, and reduced responses to sorafenib and transarterial chemoembolization treatment in HCC. Interestingly, SF3B6 was associated with variant splicing isotypes of genes involved in the G2M checkpoint and DNA repair pathways, including NEIL3, NEK2, KIF4A, TROAP, and FANCD2. Moreover, SF3B6 was highly expressed in liver cancer cells, promoting the proliferation, migration, and invasion of cancer cells, inhibiting apoptosis, and regulating the transition from the S phase to the G2M phase of the cell cycle.ConclusionWe emphasize that SF3B6 has the potential to serve as a biomarker for predicting cancer diagnosis, prognosis, and immunotherapy responses, especially in HCC. SF3B6 and its related alternative splicing isoforms promote the occurrence and progression of HCC and may serve as potential therapeutic targets.